Masyarakat Madani: Sebuah Keniscayaan - Nawiruddin Nawiruddin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
Civil society, or civil society, is an autonomous society capable of balancing the arbitrariness of elites who dominate state power. Therefore, the existence of civil society is a necessity for a democratic country. Democracy and civil society are two correlated entities. Democracy can only be upheld in civil society, and civil society cannot exist in a non-democratic society. In civil society, there are values that uphold equality, justice, and protect and respect the rights of citizens, both political, social, economic, and cultural rights.